State of Hydrogen in Idealized Carbon Slitlike Nanopores at 77 K - Kowalczyk, Piotr; Holyst, R.; Terzyk, A.; Gauden, P. (American Chemical Society, 2006)
The purpose of this letter is to clarify recent findings and answer to the question: “What is the state of hydrogen in carbon slitlike pores at 77 K?” For this purpose, we determined the volumetric density of hydrogen in idealized carbon pores of molecular dimension at 77 K and pressure up to 1 MPa. We used quantum corrected grand canonical Monte Carlo simulation. We recognized the highest volumetric density of confined hydrogen (around 71% of hydrogen liquid at boiling point) for effective pore width 5.6 Å (H* = 3.04) in the considered pressure range. Our computational results are in agreement with the calculations performed by Wang and Johnson and Rzepka et al. In contrast, we did not observe the high volumetric density of hydrogen in slitlike carbon pores exceeding the density of hydrogen liquid at the boiling point as was reported by Jagiello and Thommes. Moreover, we obtained qualitative agreement between the simulation results and some experimental findings reported by Nijkamp.